Analyzing the medium-low and low-technology firms’ innovative behavior in an emerging economy - Del Carpio Gallegos, Javier Fernando (2020)
Objetive. Design a model that shows what factors favor the development of technological innovation in manufacturing companies of medium-low and low technological intensity. Methodology. A sample of 1106 manufacturing companies that participated in the innovation surveys in 2012 and 2015 was used, applying the partial structural equations approach and estimating the invariance between the two groups. Results. The results of this study from the structural model, which allow obtaining the positive and statistically significant coefficients, which allow empirically validating the hypotheses. Conclusions. It was evidenced that non-technological innovation, absorption capacity and technological acquisition favor technological innovation in companies with low technological intensity. This article confirms that manufacturing companies should guide efforts to improve their capacity for innovation.